2009
DOI: 10.1002/wcc.6
|View full text |Cite
|
Sign up to set email alerts
|

The idea of anthropogenic global climate change in the 20th century

Abstract: People had long speculated that human activities might affect a region's climate. But a developed conjecture that humanity might change the climate of the entire planet first appeared in 1896: a calculation that carbon dioxide from fossil fuel combustion could gradually warm the globe. Scientists soon rejected the idea. Most people thought it incredible that climate could change globally except on a geological timescale, pushed by forces far stronger than human activity. In midcentury, a few scientists revived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 74 publications
(102 reference statements)
0
31
0
Order By: Relevance
“…Anthropogenic climate change emerged as one of the key topics of the public environmental agenda in the late 1980s (Weart, 2010). From 2006 onwards, media coverage of climate change faced an upsurge in all countries for which data is available (CSTPR, 2013;Holt & Barkemeyer, 2012;Fig.…”
Section: Downloaded By [Gazi University] At 04:28 03 February 2015mentioning
confidence: 99%
“…Anthropogenic climate change emerged as one of the key topics of the public environmental agenda in the late 1980s (Weart, 2010). From 2006 onwards, media coverage of climate change faced an upsurge in all countries for which data is available (CSTPR, 2013;Holt & Barkemeyer, 2012;Fig.…”
Section: Downloaded By [Gazi University] At 04:28 03 February 2015mentioning
confidence: 99%
“…Over three decades later, in 1896, Swedish scientist Svante Arrhenius maintained that doubling the amount of CO 2 in the atmosphere would lead to an increase in temperature of between 5°C and 6°C while a tripling of CO 2 would lead to an increase in temperature of between 7°C and nearly 10°C (Arrhenius, 1896). That same year fellow Swede Arvid Högbom discovered that industrial processes were contributing as much CO 2 to the atmosphere as were natural processes, which over the coming centuries could lead to significant warming (Weart, 2010). This early work was largely ignored until in the 1930s when the study of anthropogenic global warming was revived by English engineer Guy Stewart Callendar.…”
Section: The Conventionmentioning
confidence: 99%
“…Callendar concluded that observed warming in the atmosphere was the result of a 10% increase in the concentration of CO 2 in the atmosphere over the preceding century and warned that the warming would continue as the use of fossil fuels increased (Ibid). By the 1970s a scientific consensus was forming based on mounting evidence of the way in which human activities had contributed to a changing climate (Weart, 2010).…”
Section: The Conventionmentioning
confidence: 99%
“…Despite contrary propaganda in media and politics, most climatologists agree that the environmental crises are indeed anthropogenic (IPCC 2007;Steffen 2010;Weart 2010). It's likely to be a sad story -'Humans in the era of unsustainability kept dipping their greedy hands deeper into the earth's crust, extracting its stores of resources.…”
Section: Lisa Schwarzinmentioning
confidence: 99%